COMPARATIVE ANALYSIS OF ACCURACY BETWEEN CAPITAL ASSET PRICING MODEL (CAPM) AND ARBITRAGE PRICING THEORY (APT) IN PREDICTING STOCK RETURN (CASE STUDY: MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2018 PERIOD) - Try Wahyuny; Tri Gunarsih (Journal of Applied Economics in Developing Countries, 2020)
This study aims to analyze the accuracy comparison between the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT) in predicting stock return in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2015 - 2018. CAPM is a model of the relationship between risk and expected return of a security or portfolio. It can be used to determine the price of a risky asset, whereas APT is an approach in determining the price of an asset that is not only based on one variable, but many variables. The variables used in this study consist of market risk premium, inflation, exchange rates (Rp / USD), interest rates, and stock returns. The method used in sampling is purposive sampling. Based on the method, 20 samples of companies with certain criteria were obtained. The data used in this study are secondary data. Secondary data collection was obtained from the Yahoo Finance website, the Bank Indonesia website, and the Ok Stock website, which includes monthly time series data on closing stock prices and the Composite Stock Price Index (CSPI), as well as monthly time series on macroeconomic variables. Data analysis in this study uses Mean Absolute Deviation (MAD) by comparing the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT). The results of data calculations show that the Mean Absolute Deviation (MAD) value on the CAPM model has a value of 0.1096 and the APT model has a value of 0.3631. The smaller the value of Mean Absolute Deviation (MAD), it indicates that the regression model is more precise or accurate in predicting the dependent variable, namely stock returns. The results of data analysis show that the CAPM model is more precise or accurate than the APT model in predicting stock returns.Keywords: CAPM, APT, Accuracy, Stock Return